1998
DOI: 10.1159/000027274
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Staphylococcus epidermidis Growth in Some Viscoelastic Substances Containing Sodium Hyaluronate

Abstract: The aim of our study was to verify the in vitro growth of Staphylococcus epidermidis in various dilutions of some viscoelastic substances containing hyaluronic acid (Healon® and Healon GV, IAL®, BiolonTM). Serial twofold dilutions of each sterile viscoelastic substance, prepared so as to obtain a final concentration ranging from 50 to 0.78% of the product in sterile saline solution (0.85% NaCl), were taken out with a pipette that delivered 1.0 ml/tube. One hundred microliters of the S. epidermidis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, contaminated agents or surgical equipment used perioperatively may also be a source of infection 4345. In addition, perioperative variations seem to have some impact on postoperative endophthalmitis rate; different intraocular lens (IOL) materials potentially act as vectors for bacterial spread into the eye11,46,47 and viscoelastic substances, such as sodium hyaluronate, or hydroxypropylmethylcellulose may facilitate transmission of bacteria to the eye 48,49…”
Section: Pathogenesis and Clinical Presentationmentioning
confidence: 99%
“…However, contaminated agents or surgical equipment used perioperatively may also be a source of infection 4345. In addition, perioperative variations seem to have some impact on postoperative endophthalmitis rate; different intraocular lens (IOL) materials potentially act as vectors for bacterial spread into the eye11,46,47 and viscoelastic substances, such as sodium hyaluronate, or hydroxypropylmethylcellulose may facilitate transmission of bacteria to the eye 48,49…”
Section: Pathogenesis and Clinical Presentationmentioning
confidence: 99%
“…Gallenga et al [15]in their in vitro study demonstrated a significant increase in S. epidermidis growth in different dilutions of viscoelastic substances containing sodium hyaluronate. All the viscoelastics tested showed a similar behavior in the lowest dilutions.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the capability of P. aeruginosa to provoke endophthalmitis [11, 16, 17, 18, 19]and the slow removal of HPMC [5], an accurate aspiration of HPMC at the end of the operation is advisable. Previous studies [10, 15]showed the ability of various staphylococcal and streptococcal species to grow in some viscoelastic substances containing sodium hyaluronate. The use of viscoelastic substances as carriers for antibiotics has been investigated [21]and may be one of the solutions to the problem of microorganism growth in viscoelastic substances.…”
Section: Discussionmentioning
confidence: 99%